Rekomendasi Rumah Makan Malang Menggunakan Metode Fuzzy Analytical Hierarchy Process dan Technique For Order Preference by Similarity to Ideal Solution - Mohammad Toriq; Imam Cholissodin; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia is one country with a large population increasing every year in the culinary business. Then a system is needed that can recommend restaurants to customers. This problem can be solved by using Fuzzy Analytical Hierarchy Process and Technique for Order Preference methods by Similarity to Ideal Solution (F-AHP and TOPSIS). The criteria are the number of food menus, restaurant ratings, food menu prices, distance of restaurants and length of time open. This method is divided into 2 stages. The first phase of FAHP is the comparison of criteria matrix, normalization of comparison criteria matrix, weight vector, priority weight, consistency ratio, TFN matrix conversion, fuzzy synthesis matrix, defuzzification vector and ordinate and fuzzy vector normalization. The second stage is TOPSIS from decision making matrix, normalization of decision matrix, weighted normalization matrix, search for positive-negative ideal solution, distance search for ideal positive-negative solution and preference value. The results of the preference value are sorted to produce the recommended restaurant ratings. In this study involved 3 customers who had visited a restaurant. The test uses the Spearman correlation test method in determining the proximity of the results of the ranking system to the manual rating by each customer. The results of testing the level of accuracy of the system rating on customers is low, namely 0.3352, -0.1538 and third -0.3205. This shows a lack of conformity between expert choices on the system because the results of expert ratings are still not based on the specified criteria.